The Potential of Indigenous Bacteria From Various Sample Soil in Degrading Polymer Plastic Waste - Anindita Riesti Retno Arimurti; Vella Rohmayani; Nurhidayatullah Romadhon; M. Inas Riandi (Al-Hayat: Journal of Biology and Applied Biology, 2023)
The accumulation of plastic waste is one of the main problems being faced by various countries in the world. The nature of plastic which is not easily degraded naturally will consequently be buried in the soil so that it will gradually change the soil components. Plastic belongs to a group of multifunctional complex polymers which have become conventional products in all sectors of life. The use of plastic on a large scale has an effect on increasing the amount of waste, such as the types of High Density Polyethylene (HDPE) and Low Density Polyethylene (LDPE) plastics. This study aims to obtain indigenous bacterial isolated from various soil samples in the landfill area and mangrove forests in Surabaya on the degree of degradation of HDPE and LDPE plastic polymers. Two places namely the final disposal site (TPA) and the Keputih bamboo forest in Surabaya. Sampling at landfill sites and mangrove forests. Then isolate the bacteria from soil samples and plastic waste obtained. Next, purification and screening of HDPE and LDPE polymer plastic degrading bacteria. The results of the isolation succeeded in obtaining 19 types of isolates that can grow on media containing plastic, with the majority having the characteristics of bacilli, Gram negative, catalase positive, capable/incapable of fermenting glucose and lactose and having cell sizes between 1-5 µm. Screening test results obtained that isolate 2 (K1D2U2 KPH) isolated from the Keputih Final Disposal Site (TPA) was identified as a Bacillus sp., with HDPE degradation ability of 27.13% and Isolate 17 (K2D3U1 MWJ) which was isolated from the Wonorejo mangrove forest was identified as a Pseudomonas sp. with LDPE degradation ability of 21.64%. Keywords: Plastics, HDPE, LDPE, Pseudomonas sp. and Bacillus sp.